Dientes supernumerarios : reporte de 170 casos y revisión de la literatura (2002)
ABSTRACT: Teeth formed in excess of the normal number are termed supernumerary; they may also be termed supplemental if they closely resemble the adjacent teeth. They can be single or multiple, unilateral o bilateral, malformed morphologically or normal in size and shape, and erupted or impacted. Supernumerary teeth can cause several complications; these include the following: crowding, delayed eruption, diastema, rotations, cystic lesions, eruption into the floor of the nasal cavity and resorption of adjacent teeth. The hyperdontia is detected either by routine radiographic examination or as a result of well known clinical signs; may erupt normally, stay impacted, appear inverted, assume an ectopic position or resorb and disappear. Early removal of such teeth is recommended if they impede the eruption of adjacent permanent teeth. This paper review previous literature and report the outcomes of a survey of 170 cases with 242 impacted supernumerary teeth to establish guidelines concerning treatment and emphasize the importance of early diagnosis and management.